Determinants of Santri Behavior in the Formation of Healthy Santri in Islamic Boarding Schools in Batanghari Regency - Puspita Sari; Guspianto .; La Ode Reskiaddin; Solihin Sayuti (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2022)
Islamic boarding schools are known as the oldest Islamic educational institutions in Indonesia. The Iarge number of Islamic boarding schooIs in Batanghari Regency, as well as the large number of students in each pesantren make this institution a major contribution to deveIopment. The roIe of the poskestren is a form of community-based health efforts (UKBM) in the boarding schooI environment, with the principle of, by and for the boarding school residents. This study aims to determine the behavioral determinants of students in the formation of heaIthy students in Islamic boarding schooIs in Batanghari Regency. This study is a quantitative study with a cross-sectional design. This study invoIved 98 respondents who were seIected by the Proportional Random Sampling technique to be interviewed. Data anaIysis was univariate, bivariate with Chi square and muItivariate with logistic regression. The results showed that 46.9% of respondents had poor student behavior in impIementing poskestren. There is a reIationship between perceived barriers (p-vaue: 0.011) perceptions of self-efficacy (p-value: 0.047), the infIuence of teachers/ustadz (p-vaIue: 0.007), the infIuence of heaIth workers (p-vaIue: 0.020) and the behavior of students. Perceived benefits (p-vaIue: 0.210) did not have a significant reIationship with the behavior of students. The factor that had a strong infIuence on the behavior of students was the influence of teachers/ustadz with an Odds Ratio (OR= 0.323. 95% CI 0.143–0.822). There is a need fr management training and the formation of HeaIthy Santri.